Improvement the texture of nitrite-free fermented sausages using microencapsulation of fermenting bacteria. (December 2022) - Afraei, Mohammad; Soleimanian-Zad, Sabihe; Fathi, Milad
Abstract: This study aims to amend nitrite-free fermented sausage texture already produced in our laboratory using microencapsulation of fermenting probiotic bacteria Lactobacillus plantarum PTCC1896 and Lactobacillus fermentum PTCC1744 (CNF treatment) and taking place physical, chemical, and microbial analyzes in comparison with cooked fermented sausages containing 120 ppm nitrite and aforementioned microencapsulated bacteria (CN treatment) and uncooked fermented sausages containing 120 ppm sodium nitrite and free bacteria (N treatment). Different percentages of sodium alginate, inulin and maltodextrin were used to evaluate the viability of bacteria. Combination of sodium alginate 1%, inulin 3% and maltodextrin 3% (w/v each) for L. plantarum PTCC1896 and sodium alginate 1%, inulin 5%, and maltodextrin 10% (w/v each) for L. fermentum PTCC1744 showed the most protective effects. The results of colorimetry showed that the mentioned bacteria could produce the desired red color of the sausage. The moisture content of cooked samples was significantly different from N treatment ( p < 0.05). The pH of all treatments was within the desired range of microbial stability. The texture and microbial evaluation results showed that cooked treatments have better texture properties and lower microbial load during storage ( p < 0.05). Considering the effects of cooking on the texture of sausage, the appropriate survival of microencapsulated bacteria and comparing the analyzes of the three treatments, the absence of nitrite and replacing it with the mentioned bacteria had no adverse effects and brought desirable results. Therefore, it is possible to produce nitrite-free probiotic fermented sausage with suitable organoleptic properties by cooking fermented sausage.